2019
DOI: 10.1149/2.1331912jes
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy vs Voltammetry: A Voltammetric Approach to Elucidate Different Chemicals in a Range of Pharmaceutical Tablets

Abstract: Over the years, Electroanalysis has been widely applied to elucidate redox behavior of novel molecules. The selectivity and low cost are spotlight features in pharmacopeial methods of identification, that can be reached by voltammetric approaches. In this work, differential pulse voltammetric (DPV) profile and the slope of the linear regression obtained from calibration graphs along with the scan study are proposed as new perspective of identification assays. With the proposed methodology we were able to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…2A). [31][32][33][34][35][36] For redox behavior, the HB pencil revealed equal electron-transfer as that on other carbon based electrodes. Overall it may be concluded that PGE represents a cheap and disposable sensor for electrochemical measurements in comparison to other more expensive commercial carbon electrodes.…”
Section: Pencil Graphite Electrodementioning
confidence: 88%
“…2A). [31][32][33][34][35][36] For redox behavior, the HB pencil revealed equal electron-transfer as that on other carbon based electrodes. Overall it may be concluded that PGE represents a cheap and disposable sensor for electrochemical measurements in comparison to other more expensive commercial carbon electrodes.…”
Section: Pencil Graphite Electrodementioning
confidence: 88%
“…The application of electrochemical techniques in the analysis of drugs and pharmaceutical products either in biological medium has increased considerably in recent years (Table 1). [33–68] The renewed interest in electrochemical techniques can be attributed in part to more sophisticated instrumentation and increased understanding of the technique themselves. The application of different electrochemical modes in the analysis of drugs and pharmaceuticals are available for the quantification of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Phenothiazines are a large class of therapeutic agents, composed by a tricyclic structure containing nitrogen and sulfur, which are used as antipsychotic drugs for treating various mental and personality disorders. [17][18][19][20][21][22][23][24] Promethazine hydrochloride (PMZ) is one of the most consumed products of this class. PMZ has sedative, antipsychotic, antihistaminic, analgesic and anticholinergic properties.…”
mentioning
confidence: 99%